Assessing stakeholders’ needs for information from charity organisations / Saunah Zainon - Zainon, Saunah (2014)
Studies examining the extent of disclosure of NPOs remain sparse, yet it is essential to ensure accountability to stakeholders. This study was initiated to elicit stakeholders’ information needs from charity organisations. The research objectives include: to measure the extent of disclosure of information by charity organisation in Malaysia; to understand the motivating factors that drives the donors to donate; to determine reasons charity organisations disclose information about their organization and to examine the organisational-specific attributes affecting the extent of information disclosed. A Charity Organisations Reporting Index (ChORI) instrument was developed to reliably measure the extent of information disclosure. Stakeholder theory and resource dependence theory were used in the development of the index. A complete set of ChORI items were compiled and used in a survey involving 117 institutional donors. The objective of the survey was to obtain the weight of importance of the items. The extent of disclosure was then measured by using both the unweighted and weighted index of the information items. A content analysis of each organisation’s annual returns resulted in a disclosure score for each organisation. The annual returns for the financial year 2009 of 101 charity organisations were examined in order to identify the extent of disclosures provided by each organisation. The dependent variable of the study, extent of disclosure, was the ratio of an organisation’s total disclosure score to the organisation’s total possible disclosure score. Through semi-structure interviews, it was found that motivating factors that drive the donors to donate are the altruism and strategic profit maximisation motivating factors. On the other hand, accountability, transparency and legitimacy appeared to be the upmost reasons for disclosure of information from the perspective of the charity. Hierarchical regression analysis was used to determine the effect of organization-specific attributes which include internal and external governance mechanism, financial and non-financial performance, and organisational type, i.e. funded or nonfunded charity organisations. The empirical results of the study revealed that external governance mechanism and financial performance have significant positive effect on the extent of disclosure. Moreover, external governance mechanism variable was found to be a more important determinant of information disclosure. Results also revealed that public-funded charity organisations were more likely to disclose more information. This is most probably due to more stringent disclosure requirements imposed by the resource providers to public-funded charity organisations. A major contribution for future research in the field is the disclosure index instrument, ChORI which was developed in this study to measure the extent of disclosure. This study also provides a guide for best practice in charity reporting. Recommendations are made in terms of ways to improve charity disclosure for better accountability and transparency. Both managerial and policy implications are also discussed.